Cyberbullying pada remaja pengguna Tik Tok: Bagaimana peranan tipe kepribadian ekstrovert? - Latifatul Chariroh; Anrilia Ema M. Ningdiyah (INNER: Journal of Psychological Research, 2023)
Cyberbullying is an aggressive behavior that is consciously carried out by a person or group of people with the aim of disturbing, humiliating, threatening, and hurting someone (the victim) by sending or uploading messages, pictures, content, and negative comments through electronic or digital media using an internet connection. Such as email, websites, instant messaging chatrooms, and social media to cause harm, discomfort, and distress. This study was intended to examine the relationship between the extroverted personality type and the tendency of cyberbullying behavior. The participants in this study were 70 teenagers using the Tik Tok application in Surabaya. The data collection technique used purposive sampling through the distribution of online questionnaires using google Forms using the Linkert scale. The results of the study through Spearman's rho correlation test obtained a correlation score of 0.146 with a significance of p = 0.228 (p> 0.05), so it can be concluded that there is an insignificant positive relationship between the extroverted personality type variable and the cyberbullying behavior variable. It can be concluded that the two variables do not have a significant relationship so this research hypothesis is rejected.